2018
DOI: 10.7150/jca.26465
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 promotes malignant progression in squamous cell carcinoma of the head and neck

Abstract: Long non-coding RNAs (lncRNAs) are potentially critical regulators of cancer malignant behaviours. Aberrant expression and dysfunction of lncRNA PVT1 have been reported in multiple human cancers. However, its role in squamous cell carcinoma of the head and neck (SCCHN) remains largely unknown. Our current study demonstrated that PVT1 expression was increased in SCCHN. High PVT1 expression was positively correlated with SCCHN clinical parameters including T classification, clinical stages and cervical lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) play an important role in various biological and pathological processes frequently implicated in cancer, including proliferation, apoptosis, cell cycle progression, migration, and invasion [4]. Plasmocytoma variant translocation 1 (PVT1) is a long nonprotein-coding gene located at the 8q24 human chromosomal region and is commonly dysregulated in PCa [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) play an important role in various biological and pathological processes frequently implicated in cancer, including proliferation, apoptosis, cell cycle progression, migration, and invasion [4]. Plasmocytoma variant translocation 1 (PVT1) is a long nonprotein-coding gene located at the 8q24 human chromosomal region and is commonly dysregulated in PCa [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have demonstrated that lncRNAs are associated with the occurrence and development of a variety of cancers . Several lncRNAs, such as UCA1, H19, and PVT1, have been reported in human head and neck carcinoma . To identify the biological function of KCNQ1OT1 in MSSCC, we demonstrated KCNQ1OT1 was upregulated in MSSCC tissues and the IMC‐3 cell line for the first time.…”
Section: Discussionmentioning
confidence: 83%
“…[26][27][28] Several lncRNAs, such as UCA1, H19, and PVT1, have been reported in human head and neck carcinoma. [29][30][31] To identify the biological function of KCNQ1OT1 in MSSCC, we demonstrated KCNQ1OT1 was upregulated in MSSCC tissues and the IMC-3 cell line for the first time. By performing loss-of-function experiments, we discovered KCNQ1OT1 promoted cell proliferation, migration, and invasion in MSSCC.…”
Section: Discussionmentioning
confidence: 99%
“…All SCCHN tissue samples and clinical information of patients were collected in the same manner as in our previous studies . The study was approved by the Research Ethics Committee of Central South University, Changsha, China.…”
Section: Methodsmentioning
confidence: 99%
“…The western blot assay was carried out according to our previous studies . Antibody information is listed in Table .…”
Section: Methodsmentioning
confidence: 99%